New Possibilities of Tear Replacement Therapy in Patients with Dry Eye Syndrome of Various Origins - V. V. Brzheskiy; S. Yu. Golubev; I. V. Brzheskaya; V. Yu. Popov (Oftalʹmologiâ, 2019)
The artificial tears on the basis hyaluronic acid is primary importance today in dry eye syndrome (DES) treatment. In recent years, they have been supplemented Optinol® Express Moisture (0.21 %) and Optinol® Deep Moisture (0.4 %) differing concentrations of sodium hyaluronate and viscosity. The study is devoted to assessing the effectiveness of these drugs in the treatment of patients with dry eye syndrome (DES) of various etiology and severities.There were 73 volunteers with DES of various etiology: 21 — Sjogren’s syndrome, 24 — meibomian blepharitis, and 28 — perimenopause in the study. All patients were divided into 2 groups: 36 patients of the first group received instillations into conjunctival cavity of the Optinol® Express Moisture (0.21 %) and 37 patients of the second group — Optinol® Deep moistening (0.4 %).Starting from the first days of therapy, all patients had a decrease in the severity of subjective signs of DES, estimated by the value of the ocular surface disease index (OSDI). At the same time, tendency to stop of the degenerative changes in the epithelium of the ocular surface was established. It is characterized by a decrease in the degree of staining. The increasement of the tear film stability and an index of the tear meniscus was found in all patients. The dynamics of the controlled parameters increased, as the instillation of the drugs took place and by the 30th day of therapy. There were significant differences from the baseline values. At the same time, the Optinol® Express Moisture (0.21 %) was more effective (mainly in terms of subjective discomfort and the severity of degenerative changes in the epithelium of the ocular surface) in patients with mild and extremely severe form of the xerosis process.The drug Optinol® Deep Moisture (0.4 %) was more effective in patients with xerosis of moderate severity and severe by the same parameters. In the course of research, we have not observed any side effects of both drugs. It allows us to recommend the drugs Optinol® Express Moisture (0.21 %) and Optinol® Deep Moisture (0.4 %) to widespread clinical use in treating patients with DES of various etiology.